Perubahan Tanda Vital sebagai Gejala Rasa Cemas sebelum Melakukan Tindakan Pencabutan Gigi pada Mahasiswa Profesi Klinik Bedah Mulut RSGM Universitas Jember (The Alteration of Vital Sign as Students’ Anxiety Symptoms before Performing Tooth Extraction in - Farrahdina Nuri Arini; Winny Adriatmoko; Masniari Novita (UPT Percetakan dan Penerbitan Universitas Jember, 2017)
Background:: First extraction performed by students of the oral surgery department givemany pressure causing body's responses such as increasing of blood pressure, pulserate, and respiratory rate. In severe rate, the outcome of the treatment may be affected bythis condition. The aim of the study to determine the alteration of vital sign as students’anxiety syndroms before performing tooth extraction in dental surgery department.Methods : This was a descriptive study of students of oral surgery department who willperform first tooth extraction. After sign an informed consent then performed themeasurement of blood pressure, pulse, and respiratory rate for 5 times, before the dayperforming extraction, before performing the examination on patient, before performinganesthesia, before performing extraction, and after performing the extraction. Result andconclusion : Students of the oral surgery department Dentistry University of Jembershowed increasing the vital sign status (blood pressure, pulse, and respiratory rate)before performing first tooth extractionKeywords : Tooth extraction, anxiety, vital sign, oral surgery.